Cambridge certificate in advanced English 4 : - Carne, Paul (Cambridge Univ. Press, 2000)
This collection of four complte practice tests comprises past papers from the Cambridge Certificate in Advanced English examination, specially adapted by the University of Cambridge Local Examinations Syndicate to reflect the most recent CAE specifications.